Failure Analysis of Superheater Tubes Made from Material T91 in the Boiler of a 600 MW Power Plant - Khabib Abdul Munif (JMES: The International Journal of Mechanical Engineering and Sciences, 2020)
This paper highlights a study for the failure investigation of superheater tubes made of the material T-91 of a boiler in the coal-fired power plant. Two tubes are subjected to different types of failure. Visual examination, dimensional measurement, and chemical analysis are conducted as part of the study. Apart from these, the hardness test and microstructural analysis are also conducted to ascertain the possible cause of failure. The superheater tube material cracking, cavity until broken failure that occurred on the first tube was resulted in thick lip rupture and the second tube resulted in thin lip fish mouth rupture. Creep deformation, localized rapid overheating, surface tube erosion, and fly ash of coal corrosion are the main cause of tube failure. It can be avoided by regularly and according to standards cleaning the scale or deposit on the surface of the tube.